2016
DOI: 10.1364/josaa.33.000160
|View full text |Cite
|
Sign up to set email alerts
|

Ray and wave aberrations revisited: a Huygens-like construction yields exact relations

Abstract: The aberrations of an optical system can be described in terms of the wave aberrations, defined as the departure from the ideal spherical wavefront; or the ray aberrations, which are in turn the deviations from the paraxial ray intersections measured in the image plane. The classical connection between the two descriptions is an approximation, the error of which has, so far, not been quantified analytically. We derive exact analytical equations for computing the wavefront surface, the aberrated ray directions,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…(2a) and (2b) , have errors of a fifth order. Restrepo et al [1] found that Eqs. (2a) and (2b) thus yield large errors for systems with large numerical apertures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(2a) and (2b) , have errors of a fifth order. Restrepo et al [1] found that Eqs. (2a) and (2b) thus yield large errors for systems with large numerical apertures.…”
Section: Discussionmentioning
confidence: 99%
“…where R reference and ๐œ‰ โ€ฒ are the radius and refractive index of the reference sphere, respectively. As discussed by Restrepo et al [1], Eqs. (16a) and (16b) inevitably induce errors as a result of their approximate nature.…”
Section: (15f)mentioning
confidence: 90%
See 3 more Smart Citations